Integrated electronics designs and systems - Mukhzeer Mohammad Shahimin; Noraini Othman (Penerbit Universiti Malaysia Perlis, 2013)
This book systematically examines various subject areas important to integrated electronics and should be an excellent desk reference for electronics engineers interested in gaining an overview of this emerging field.